Toe keloid after nail extraction treated with surgical excision: A case report. Issue 51 (December 2017) - Liu, Hao; Song, Kexin; Zhang, Mingzi; Dong, Xinhang; Liu, Shu; Wang, Youbin
Abstract: Rationale: In this study, a case of toe keloid after nail extraction is presented, in which the keloids on both toes were resected by surgical excision. Keloids (from the Greek word meaning "crab's claw") are fibrous growths that extend beyond the original area of injury to involve the adjacent normal skin. In general, keloid tendencies appear to be regionally isolated to keloid-prone areas, such as the chest, ears, and deltoid regions, whereas the hands and feet are usually spared, which is why this case is meaningful. Patient concerns: A 20-year-old Chinese man had paronychia on both halluxes when he was 16 years old. He underwent a nail extraction at the age of 17. The nails of both halluxes were removed by nail extraction. This operation was successful, and the postoperative course was uneventful. After 6 months, the scars of the nail extraction on both sides began to exhibit hyperplasia and became red and swollen with itching. Later, the scar expanded and eroded the tissue beyond the matrix unguis. The whole matrix unguis was destroyed, and the nails were distorted. The scars began to ulcerate after 2 years. The patient used potassium permanganate to clean his wounds, but the keloid scars did not improve. Diagnoses: The patient was diagnosed as toe keloid based on his history and symptoms. The biopsy result supported our diagnoses. Interventions: The toe keloids were effectively cured by surgical excision and skin flap transplantation combined with postoperative irradiation and hyperbaric oxygen (HBO) treatment. Outcomes: No recurrence was detected during the period from 6 to 24 months of follow-up after the surgery. Lessons: In this case, the trauma of the nail extraction was likely the key cause of the keloid. However, the patient was also predisposed to keloids, as we observed keloids on his chest. In general, keloid tendencies appear to be regionally isolated to keloid-prone areas such as the chest, ears, and deltoid regions, whereas the hands and feet are usually spared, which is why this case is meaningful.